2015
DOI: 10.12816/0017965
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Enoxaparin on Bleeding after Coronary Artery Bypass Surgery

Abstract: de l'énoxaparine reçue en préopératoire sur le saignement après chirurgie de pontage coronarien.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…The inhibition of coagulation function of heparin was prohibiting the activation of thrombin, factor Xa and other clotting enzymes, the anticoagulant function of heparin deeply depended on antithrombin III, binding it and developing an anticoagulant complex, and the complex could increase the anticoagulant function more than one thousand times. However, it seems LMWH has become more popular and replaced heparin in many clinical indications due to the more predictable pharmacokinetic and pharmacodynamic properties (13,22). These findings were also pro our results that administration of LMWH was prior to heparin regarding bleeding related events.…”
Section: Discussionsupporting
confidence: 79%
“…The inhibition of coagulation function of heparin was prohibiting the activation of thrombin, factor Xa and other clotting enzymes, the anticoagulant function of heparin deeply depended on antithrombin III, binding it and developing an anticoagulant complex, and the complex could increase the anticoagulant function more than one thousand times. However, it seems LMWH has become more popular and replaced heparin in many clinical indications due to the more predictable pharmacokinetic and pharmacodynamic properties (13,22). These findings were also pro our results that administration of LMWH was prior to heparin regarding bleeding related events.…”
Section: Discussionsupporting
confidence: 79%
“…However, heparin could also bind to cells and plasma proteins, which could lead to side effects of heparin-induced thrombocytopenia and osteoporosis (15). Thus, LMWH, which has more predictable pharmacokinetic and pharmacodynamic properties, has become more popular and replaced heparin in many clinical indications (15,17). Recent studies have compared the thromboprophylaxis efficacy of heparin with that of LMWH and found that LMWH was as effective as heparin for VTE prevention (18,19) and was even superior in PE prevention to heparin (20).…”
Section: Discussionmentioning
confidence: 99%